Selective approach towards robust control and accommodation of disturbances. (1st January 2014) - Er, Poi Voon; Cao, Rongmin; Liang, Wenyu; Yang, Rui; Teo, Chek Sing; Tan, Kok Kiong
Precision control is desirable in high performance robotics and automation systems. However, when extraneous disturbances step in, persistence with a precision control methodology can result in an unacceptable level of performance when the nominal conditions under which the nominal control is designed no longer hold. At this time, a suitable adaptive and robust control scheme would be useful to cope with the evolving situation with disturbances though it may not yield the same level of nominal control performance. Resolving these conflicting requirements in an appropriate and calculated manner during the course of operation of a motion system becomes an important issue to address to accommodate the disturbances and yield the best level of performance possible. In this paper, we present a selective approach towards commissioning a good compromise between nominal and appropriate robust adaptive control. The approach leverages on a sensor fusion method based on radial basis functions (RBFs) to provide a control selector signal indicative of the level of disturbance present to fire the appropriate control. Simulation results based on the model of a real linear motion system setup are provided to show the effectiveness of the approach.